The Clinical Role of miRNAs in the Development and Treatment of Glioblastoma - Epistolio, Samantha; Spina, Paolo; Zaed, Ismail; Cardia, Andrea; Marchi, Francesco; Frattini, Milo (International journal of molecular sciences, 2025)
Glioblastoma multiforme (GBM) is the most common brain tumor and one of the most aggressive, with a median overall survival (OS) of only 15–18 months. These characteristics make it necessary to identify new targets for the improvement of prognosis and better prediction of response to therapies currently available for GBM patients. One possible candidate target could be the evaluation of miRNAs. miRNAs are small non-coding RNAs that play important roles in post-transcriptional gene regulation. Due to their functions, miRNAs also control biological processes underlying the development of GBM and may be considered possible targets with a clinical role. This narrative review introduces the concept of miRNAs in GBM from a clinical and a molecular perspective and then addresses the specific miRNAs that are most described in the literature as relevant for the development, the prognosis, and the response to therapies for patients affected by GBM.